Seasonal distribution and sex ratio of five noctuid species (Insecta, Lepidoptera) captured in blacklight traps on São Miguel - Azores - Silva, Michael (2011)
The adult flight periods of Agrotis ipsilon (HÜFNAGEL), Agrotis segetum (DENNIS & SCHIFERMÜLLER), Noctua pronuba LINNAEUS, Peridroma saucia (HÜBNER) and Xestia c-nigrum (LINNAEUS) (Lepidoptera, Noctuidae) were studied between July of 1988 and December of 1989, at Ribeira Grande, Arribanas and Lagoa do Congro on the island of São Miguel, using Pennsylvania blacklight traps. While there was evidence of considerable fluctuations in density, A. ipsilon, A. segetum, P. saucia and X c-nigrum were present continuously at the three locations. In contrast N. pronuba was only captured between July and September. For any given species both sexes were captured simultaneously. In X c-nigrum males were more frequent than females while in the other species females were more abundant. However, in no case does the sex-ratio deviates entirely from 1:1.